Hybrid sorption thermal–battery storage in photovoltaic greenhouses: Toward net-zero energy and reduced battery stress - Mohammadreza Gholami (17032317) (2026)
Greenhouse energy demand in arid regions is exceptionally high due to extreme outdoor temperatures and intensive cooling requirements, making reliable and efficient energy supply a critical challenge. Sorption Thermal Energy Storage (SoTES) can capture and release excess heat with high efficiency, offering long-term thermal savings and significant cooling load reduction. When integrated into semi-transparent photovoltaic (STPV) greenhouses, SoTES serves as an effective complement to Battery Energy Storage Systems (BESS), which primarily address short-term electricity shifting. This study investigates a hybrid active–passive storage configuration in which BESS stores surplus STPV electricity for later use, while SOTES harnesses excess solar heat to offset cooling demand and supply heating during cooler periods. A comprehensive mathematical model was developed for solar irradiance distribution, STPV output, BESS operation, and SoTES performance, embedded within a multi-objective optimization framework using the Tribe Intelligence Evolutionary Optimizer (TIEO) to balance reductions in energy dependency (ED) and improvements in net present value (NPV). Results show that the hybrid system can reduce annual ED by 19.2% compared to the STPV-only case (with 12.8% attributed to SoTES and 6.4% to BESS). Moreover, SoTES reduces BESS cycling frequency by nearly 30% and average depth of discharge by 12%, highlighting its role in indirectly extending battery lifetime and improving economic viability. Overall, combining short-term electrical storage with long-term thermal storage offers a resilient and economically viable pathway toward greenhouse energy autonomy in extreme climates. Other Information Published in: Journal of Energy Storage License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.est.2026.122254